Local Government Roles in School-Based Hypertension Prevention Among Adolescents in Tasikmalaya City - Suprapti, Betty; Yuningsih, Aneng; Kurnia, Anih; Gustiani, Mia Ruhmiati; Asparina, Arina; Ismawi, Ade Sayid; Purnama Sari, N.Jihan Audiya (JURNAL VNUS (Vocational Nursing Sciences), 2025)
Adolescent hypertension has become a global public health concern due to its potential to increase the risk of cardiovascular diseases in adulthood. Early prevention efforts through school-based initiatives are essential; however, policy implementation at the local level continues to face significant challenges. This study aims to analyze the role of the Tasikmalaya City local government in school-based hypertension prevention among adolescents. A qualitative case study design was employed, with data collected through in-depth interviews, focus group discussions, observations, and document reviews. Participants consisted of officials from the Health and Education Departments, school principals, teachers, healthcare workers from community health centers, and student representatives. Data were analyzed thematically using NVivo software for coding. The findings show that the local government has implemented several programs, including non-communicable disease screening, Posyandu Remaja (Youth Integrated Health Post), Usaha Kesehatan Sekolah (School Health Unit/UKS), and Promosi Kesehatan Reproduksi Remaja (Adolescent Reproductive Health Promotion). Key barriers identified include a limited number of healthcare workers, inadequate facilities, budget constraints, and uneven program outreach. Nevertheless, opportunities for improvement were observed through the planned development of a Mayor’s Regulation, strengthened intersectoral coordination, and the empowerment of school health cadres. This study concludes that while the local government has taken steps toward adolescent hypertension prevention, efforts remain suboptimal and require enhanced local policies, resource allocation, and multisector collaboration to improve program effectiveness. Overall, the study contributes to strengthening evidence on the role of local governments in implementing adolescent health policies at the school level in Indonesia.